2022
DOI: 10.1088/1741-2552/ac456e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality-based motor rehabilitation: a systematic review of fMRI studies

Abstract: Background: The use of virtual reality (VR) as a rehabilitation tool has been shown to induce motor and cognitive improvements in different populations. Functional magnetic resonance imaging (fMRI) has been used to investigate neuroplasticity resulting from these treatments. We hypothesize that VR rehabilitation induces functional improvement and brain changes that can be detected by fMRI. Objective: To systematically review the effects of VR intervention on the cortical reorganization measured by fMRI and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…42 Some studies used VR to interact three-dimensional virtual environment. 4,25,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] We also found studies using Robotic-assisted gait training for PD. 24,29,[59][60][61][62] We analyzed several types of AP and categorized them into commercial and non-commercial devices available for research, rehabilitation, or home-based care.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…42 Some studies used VR to interact three-dimensional virtual environment. 4,25,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] We also found studies using Robotic-assisted gait training for PD. 24,29,[59][60][61][62] We analyzed several types of AP and categorized them into commercial and non-commercial devices available for research, rehabilitation, or home-based care.…”
Section: Resultsmentioning
confidence: 70%
“…Studies observed that VR rehabilitation may improve neuroplasticity and change brain neural patterns by activation and reorganization mainly of the primary motor cortex, sensorimotor cortex, and supplementary motor area. 48 In addition, functional magnetic resonance imaging showed that PD patients who underwent VR training increased activity in the precuneus region, which is linked to visuospatial integration, memory, and self-awareness, and this network is active during activities involving memory encoding and retrieval. 47 Cognition plays an important role in postural control and may interfere with gait and posture assessment and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological imaging tended to obtain information from multiple modalities and integrate them and combined with different advantages of modal imaging technology so as to obtain more comprehensive, rich, accurate, and reliable brain information, and this method also provides a new monitoring method for the description of the cognitive neural dynamic process ( 45 ). VR-associated neurophysiological changes can be assessed by non-invasive and portable neuroimaging techniques including fMRI ( 46 ) and/or EEG ( 47 ) to determine changes in cerebral hemodynamic responses or oscillating brain waves, respectively. In particular, the use of fMRI as a measure of cerebral hemodynamic response to the neurological rehabilitation process has received attention.…”
Section: Discussionmentioning
confidence: 99%
“…The basic neuroscience behind VR-based treatment has mainly been linked to functional brain remodeling ( Feitosa et al, 2022 ). The present study also set the imaging ROIs in the emotional networks, as reported previously, to explore the functional remodeling induced by VR supporting emotion recovery.…”
Section: Discussionmentioning
confidence: 99%